Evaluating different scenarios for optimizing energy consumption to achieve sustainable green building in malaysia - Assadi, M.K. (Asian Research Publishing Network, 2016)
One of the most users of energy in the construction industry is residential buildings that use the high value of energy. Because of the high effect of construction activities on environment, serious attention should be given to sustainability concept in construction activities. There are climate factors such as temperature, humidity and pressure that have a considerable effect on the sustainability of green buildings based on energy consumption. The main goal of this paper is to achieve a sustainable green building by optimizing the energy consumption based on two significant factors which are temperature and humidity. To achieve this goal, the design of experiments (DOE) and building simulation are applied. A two-storey house in Malaysia was selected as the case study. The final result shows that to achieve the optimum value of cooling load to have a sustained design of green residential buildings all the significant factors should be placed on a low level which it means that temperature and humidity should be equal to 20 degrees Celsius and 60 respectively. Â©2006-2016 Asian Research Publishing Network (ARPN).